Pengaruh Komunikasi Interpersonal pada Pilihan Destinasi Wisata Studi Kasus Film 500 Days of Summer - Handya Aulia Dananjaya; Muhammad Pandu Sakha Setiawan; Mohammad Imam Al Baihaqi; Damon Pius Wiryatmoko; Trisakti Trisakti; Arsih Amalia Chandra Permata; Wiyata Wiyata (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
The movie 500 Days of Summer represents the complexity of interpersonal communication in romantic relationships through a multidimensional and realistic approach. This study analyzes the communication dynamics between the main characters, Tom Hansen and Summer Finn, by focusing on the misalignment of verbal and nonverbal messages that trigger ambiguity and miscommunication. In addition, this study explores the implications of the emotional dynamics in the relationship for tourist behavior, especially the phenomenon of emotional tourism as a form of escape and recovery after a breakup. This study also examines the utilization of emotional experience-based tourism as a destination marketing strategy to meet the needs of tourists in emotional transition. The results of the analysis confirm the importance of integrating an understanding of interpersonal communication and emotional dynamics in the development of tourism oriented towards affective and reflective experiences. The findings provide an academic contribution to the study of interpersonal communication and its implications in the tourism industry, particularly in designing destinations that are responsive to the psychological needs of visitors.